Echocardiography-guided percutaneous intramyocardial alginate hydrogel implants for heart failure: canine models with 6-month outcomes - Ma, Hui; Gong, Wenqing; Lim, D. Scott; Li, Jing; Ta, Shengjun; Hu, Rui; Li, Xiaojuan; Zheng, Minjuan; Liu, Liwen (Frontiers in Cardiovascular Medicine, 2024)
Background Echocardiography-guided percutaneous intramyocardial alginate-hydrogel implantation (PIMAHI) is a novel treatment approach for heart failure (HF). We validated PIMAHI safety and efficacy in canine HF models. Methods Fourteen canines with HF [produced by coronary artery ligation, left ventricular ejection fraction (LVEF) < 35%] were randomised to PIMAHI treatment (n = 8) or controls (n = 6). Echocardiography, two-dimensional speckle tracking echocardiography, and pathological examinations after a 6-month follow-up were performed. Repeated-measures analysis of variance was used for within-group comparisons. Results At 6-month follow-up, PIMAHI treatment reversed LV dilation and remodelling, increasing LV free wall thickness (LVFW, p = 0.002) and interventricular septum thickness (IVS, p < 0.001) and reducing LV end-diastolic volume (EDV, p = 0.008) and end-systolic volume (ESV, p = 0.004). PIMAHI significantly improved LV systolic function, increasing LVEF (EF, p = 0.004); enhanced LV myocardial contractility, including increased LV global longitudinal strain (GLS, p < 0.001), global circumferential strain (GCS, p = 0.006), and mitral annulus displacement (MAD, p = 0.001). Compared with controls at 6-month, PIMAHI group significantly increased LVFW thickness (8.5 ± 0.3 vs. 6.8 ± 0.2 mm, p = 0.002) and IVS (7.9 ± 0.1 vs. 6.1 ± 0.2 mm, p < 0.001); decreased LVEDV (30.1 ± 1.6 vs. 38.9 ± 4.5 ml, p = 0.049) and ESV (17.3 ± 1.2 vs. 28.7 ± 3.6 ml, p = 0.004); increased LV systolic function (42.7 ± 1.5 vs. 26.7 ± 1.1% in EF, p = 0.001); and enhanced LV myocardial contractility including GLS (13.5 ± 0.8 vs. 8.4 ± 0.6%, p = 0.002), GCS (16.5 ± 1.4 vs. 9.2 ± 0.6%, p = 0.001), and MAD (11.4 ± 3.5vs 4.6 ± 2.5 mm, p = 0.003). During PIMAHI treatment, no sustained arrhythmia, pericardial, or pleural effusion occurred. Conclusions PIMAHI in canine HF models was safe and effective. It reversed LV dilation and improved LV function.